Lack of a p21waf1/cip-Dependent G1/S Checkpoint in Neural Stem and Progenitor Cells After DNA Damage In Vivo - Roque, Telma; Haton, Céline; Etienne, Olivier; Chicheportiche, Alexandra; Rousseau, Laure; Martin, Ludovic; Mouthon, Marc-André; Boussin, François D. (Stem cells (Dayton, Ohio), 2012)
The cyclin‐dependent kinase inhibitor p21waf1/cip mediates the p53‐dependent G1/S checkpoint, which is generally considered to be a critical requirement to maintain genomic stability after DNA damage. We used staggered 5‐ethynyl‐2′deoxyuridine/5‐bromo‐2′‐deoxyuridine double‐labeling in vivo to investigate the cell cycle progression and the role of p21waf1/cip in the DNA damage response of neural stem and progenitor cells (NSPCs) after exposure of the developing mouse cortex to ionizing radiation. We observed a radiation‐induced p21‐dependent apoptotic response in migrating postmitotic cortical cells. However, neural stem and progenitor cells (NSPCs) did not initiate a p21waf1/cip1‐dependent G1/S block and continued to enter S‐phase at a similar rate to the non‐irradiated controls. The G1/S checkpoint is not involved in the mechanisms underlying the faithful transmission of the NSPC genome and/or the elimination of critically damaged cells. These processes typically involve intra‐S and G2/M checkpoints that are rapidly activated after irradiation. p21 is normally repressed in neural cells during brain development except at the G1 to G0 transition. Lack of activation of a G1/S checkpoint and apoptosis of postmitotic migrating cells after DNA damage appear to depend on the expression of p21 in neural cells, since substantial cell‐to‐cell variations are found in the irradiated cortex. This suggests that repression of p21 during brain development prevents the induction of the G1/S checkpoint after DNA damage. STEM CELLS 2012;30:537–547